Telecommunications sector policy (the Government of the Commonwealth of the Bahamas Nassau, 2002)
Outlines the importance of a telecommunications sector to The Bahamas. Sets out the fundamental objectives which are to be achieved. Sets out also the policy framework for the newly privatised and liberalised telecommunications sector. Describes briefly, the main outlines of the new regulatory structure and some major regulatory features of this sector.
Keywords: TELECOMMUNICATIONS